Students’ Perception on Youtube as a Tool for Learning English Speaking Skills Among English Education Students at Batanghari University - Nabila, Syarifah; Munawwaroh, Khidayatul; Fitri, Nurul (JELT: Journal of English Language Teaching, 2025)
This study looks into how students see YouTube as an extra tool to help them improve their English Speaking skills at Batanghari University. It focuses on four main aspects: vocabulary, grammar, pronunciation, and fluency. The research used a qualitative case study method, with interviews conducted with 10 students who actively use YouTube in their learning process. The results show that YouTube can support vocabulary growth, grammar awareness, and pronunciation practice through exposure to authentic language and engaging content. Its impact on fluency is mixed some students feel more confident and speak more naturally, while others still struggle with hesitation due to factors like fast-paced speech or unfamiliar accents. The results of the research are students perception on the use of YouTube for learn English is positive, from YouTube they can learn anything especially for speaking skills. Also YouTube can make students good pronounce, increase students vocabulary, it helpful for grammar but less helpful for fluently. Overall, YouTube is considered a useful addition to learning, especially when paired with interactive practice and teacher guidance.